The Contribution of Indonesian Women's Eating Habit to Iron Deficiency Anemia - Zahrulianingdyah, Atiek (Pakistan Journal of Nutrition, 2016)
Iron nutrition anemia is a major problem in Indonesia, especially for women who are of reproductive age. Based on previous studies, women have less healthy diets, which impacts anemia. This study was aimed at describing eating behavior in women from various aspects in depth. This study reviewed related articles and books to describe eating behavior in women from various aspects in depth. It is necessary to study the eating behavior in women from various aspects in depth. Anemia is a term used to refer to a state of decline in hemoglobin concentration in the blood caused by a lack of iron required for the formation of hemoglobin. Hemoglobin is made by red blood cells, whose primary function is to carry oxygen to all parts of the body. Thus, this substance is vital and needed in particular for women of childbearing age. Hemoglobin formation is strongly affected by iron intake. Modifying eating habits is recommended for women of productive age.